2022
DOI: 10.1155/2022/2760537
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Modulates the Migration of Retinal Pericytes Induced by Advanced Glycation End Products

Abstract: Retinal pericyte migration occurs in the early stage of diabetic retinopathy (DR), which is one of the important causes of pericyte loss. Autophagy has been found to play essential roles in the regulation of many types of cell migration. In this study, we explored the relationship between autophagy and retinal pericyte migration. In diabetic rats, the retinas became thinner, and the level of autophagy in each cell layer increased. In the primary culture of bovine retinal pericytes, we found that advanced glyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Previous data have confirmed the inevitable role of autophagy on bovine retinal pericyte migration in in vitro conditions ( Lin et al, 2022 ). The exposure of bovine retinal pericytes to advanced glycation end products (AGEs) led to autophagy activity (LC3-II/LC3-I ratio↑, and P62↓) and enhanced migration properties without changes in the survival rate.…”
Section: Role Of Autophagy In Pericyte Activitysupporting
confidence: 56%
See 2 more Smart Citations
“…Previous data have confirmed the inevitable role of autophagy on bovine retinal pericyte migration in in vitro conditions ( Lin et al, 2022 ). The exposure of bovine retinal pericytes to advanced glycation end products (AGEs) led to autophagy activity (LC3-II/LC3-I ratio↑, and P62↓) and enhanced migration properties without changes in the survival rate.…”
Section: Role Of Autophagy In Pericyte Activitysupporting
confidence: 56%
“…The exposure of bovine retinal pericytes to advanced glycation end products (AGEs) led to autophagy activity (LC3-II/LC3-I ratio↑, and P62↓) and enhanced migration properties without changes in the survival rate. In retinal pericytes, the production of metalloproteinase-2 (MMP-2) and phosphorylation of focal adhesion kinase (FAK) were elevated ( Lin et al, 2022 ). Of note, incubation of these cells with chloroquine, an autophagy inhibitor, can blunt the increase of FAK and MMP-2.…”
Section: Role Of Autophagy In Pericyte Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that the thickening of collagen fibers may be partially a compensatory response to AGE. 36 Studies have reported that AGE can directly cross-link with vascular BM proteins and lead to BM thickening; 33 ; AGE in ECs and pericytes can directly impair the conformation and function of intracellular proteins, and result in endothelial dysfunction; 33 , 37 ; AGE can exert a stimulatory role in endothelial cell production of VEGF, which is involved in the development of diabetic retinopathy. 33 These suggested that vasculopathy in the diabetic pulp may be attributable to the AGE accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…It participated in the signal transition from focal adhesion to conditional cytoskeleton dynamics . Conversely, the migratory cell ability is accompanied by a decrease in vinculin expression . In recent years, the downregulation of vinculin has been found in several highly metastatic cancer cells, which reminded us of its unique role in metastasis and relapse. However, few efforts about vinculin were made in occupational diseases; the vinculin expression level in plasma has not been studied thoroughly compared with other tissues or cells, either.…”
Section: Discussionmentioning
confidence: 99%